Performance of the 2016 ACR-EULAR Myositis Response Criteria in adult dermatomyositis/polymyositis therapeutic trials and consensus profiles - Saygin, Didem; Kim, Hanna; Douglas, Christian; Erman, Brian; Wilkerson, Jesse; McGrath, John A; Oddis, Chester V; Lundberg, Ingrid E; Amato, Anthony A; García-De La Torre, Ignacio; Chinoy, Hector; Fiorentino, David; et al. (Rheumatology (Oxford, England), 2023)
OBJECTIVE: The ACR-EULAR Myositis Response Criteria (MRC) were developed as a composite measure using absolute percentage change in six core set measures (CSMs). We aimed to further validate the MRC by assessing the contribution of each CSM, frequency of strength vs extramuscular activity improvement, representation of patient-reported outcome measures (PROM), and frequency of CSM worsening. METHODS: Data from adult dermatomyositis/polymyositis patients in the rituximab (n = 147), etanercept (n = 14), and abatacept (n = 19) trials, and consensus patient profiles (n = 232) were evaluated. The Total Improvement Score (TIS), number of improving vs worsening CSMs, frequency of improvement with and without muscle-related CSMs, and contribution of PROM were evaluated by MRC category. Regression analysis was performed to assess contribution of each CSM to the MRC. RESULTS: Of 412 adults with dermatomyositis/polymyositis, there were 37%, 24%, 25%, and 14% with no, minimal, moderate, and major MRC improvement, respectively. The number of improving CSMs and absolute percentage change in all CSMs increased by improvement category. In minimal-moderate improvement, only physician-reported disease activity contributed significantly more than expected by MRC. Of patients with at least minimal improvement, 95% had improvement in muscle-related measures and a majority (84%) had improvement in PROM. Patients with minimal improvement had worsening in a median of 1 CSM, and most patients with moderate-major improvement had no worsening CSMs. Physician assessment of change generally agreed with MRC improvement categories. CONCLUSION: The ACR-EULAR MRC performs consistently across multiple studies, further supporting its use as an efficacy end point in future myositis therapeutic trials.
Keywords: dospělí; Dermatomyositis; PM; Adult; výsledek terapie; outcome measure; lidé; outcome assessment; konsensus; Treatment Outcome; myozitida; Consensus; DM; myositis; Polymyositis; polymyozitida; Myositis; clinical trial; response criteria; dermatomyozitida; Humans